Trasmission electron microscopy of partially dissolved exines of Pseudotsuga menziesii (MlRB.) FRANCO - Kedves Miklós (Plant cell biology and development, 2000)
Pollen grains of Pseudotsuga menziesii (MIRB.) FRANCO were partially dissolved with organic solvents and investigated with transmission electron microscope. In this paper the most important TEM results of the partially dissolved exines are presented. The resistance of the exine may be pointed out in particular against diethylamine. The very early exine ultrastructure of the recent Pseudotsuga genus was compared with the ultrastructure data of fossil pollen grains.